2020
DOI: 10.1186/s12885-020-06760-1
|View full text |Cite
|
Sign up to set email alerts
|

CD45dimCD34+CD38−CD133+ cells have the potential as leukemic stem cells in acute myeloid leukemia

Abstract: Background: Leukemia stem cells (LSCs) in play an important role in the initiation, relapse, and progression of acute myeloid leukemia (AML), and in the development of chemotherapeutic drug resistance in AML. Studies regarding the detection of LSCs and the development of novel therapies for targeting them are extensive. The identification of LSCs and targeting therapies for them has been continuously under investigation. Methods: We examined the levels of CD45 dim CD34 + CD38 − CD133 + cells in bone marrow sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…There are too few HSC-like cells to effectively characterize NPM1 -mediated derailment, so we enriched the immature population in NPM1 mut patients. Specifically, we identified two differentially expressed genes in this population that code for surface proteins, namely CD34 (log fold change: 6.67, adjusted p < 1e-6) and a less-conventional marker, PROM1 (CD133 54 ; log fold change = 7.23, adjusted p < 1e-6), and sorted for cells expressing either CD34 or PROM1. This approach successfully expanded the target population in patient AML1 from 160 to 37,395 cells ( Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There are too few HSC-like cells to effectively characterize NPM1 -mediated derailment, so we enriched the immature population in NPM1 mut patients. Specifically, we identified two differentially expressed genes in this population that code for surface proteins, namely CD34 (log fold change: 6.67, adjusted p < 1e-6) and a less-conventional marker, PROM1 (CD133 54 ; log fold change = 7.23, adjusted p < 1e-6), and sorted for cells expressing either CD34 or PROM1. This approach successfully expanded the target population in patient AML1 from 160 to 37,395 cells ( Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The identification of these cells can be performed through immunophenotyping, where it is possible to differentiate HSCs from LSCs. From this differentiation, counting methods are performed (78)(79)(80).…”
Section: Presence Of Lscs and Relapsementioning
confidence: 99%
“…Furthermore, transcriptomic analysis done on purified HSCs from myelodysplastic syndrome (MDS) patients and age-matched cord blood cell HSC controls identified selective overexpression of CD99 on LSCs, and that CD99 is at a particularly high level at relapse when compared to samples obtained at time of diagnosis, suggesting a potential link between CD99 expression and the chemo-resistant properties of LSCs in general [ 30 ]. Furthermore, a study conducted by Heo and colleagues reported prominent enrichment of the CD45 dim CD34 + CD38 − CD133 + cells in BM of AML patients, and that this unique signature is associated with poor prognosis; however, functional validation of LSC activities of these cells is still needed [ 31 ]. Another factor that complicates the already heterogenous landscape of AML LSC surface antigen expression is the stage during which leukemic transformation occurs, as recent evidence reported transformation may also take place in mature granulocyte–macrophage precursors without expressing CD34, specifically in those samples with NPM1 mutation [ 32 , 33 , 34 ].…”
Section: The Discovery and Cellular Properties Of Leukemic Stem Cells...mentioning
confidence: 99%